AN ANALYSIS OF FACTORS INFLUENCING THE QUALITY OF HOUSING CONSTRUCTION PROJECTS IN THE WESTERN CAPE, SOUTH AFRICA - Fore, Stanley (MATTER: International Journal of Science and Technology, 2015)
Quality measurement is the trigger for quality improvement; things that cannot be measured therefore can be improved. The result of poor quality in the house hold construction projects in the Western Cape hence might be the lack of quality measurement methods or standards. The research intended to provide clients, building inspectors, building inspectors, project managers, designers and contractors with the necessary information needed to better manage the quality of house hold construction projects in the Western Cape Province. Factors that affect the quality of house hold construction projects during the construction phase were identified. The use of hybrid was implemented in order to exhaust all possible ways to obtain data and questionnaires were developed and used as research tools to obtain the opinions of respondents that included the contractors, building inspectors, household and project managers, on the factors affecting construction projects and how these factors can methodology be addressed to ensure the construction of quality buildings. It was concluded that the most important factors affecting the quality of house hold constructions projects are, the skills and experience of contractors and project managers, site lay-outs, materials, equipment used, Mediterranean weather conditions, lead time in decision making. Therefore the authors recommend that the construction industry should have a stand-alone board that deals with quality standards and controls the quality standards of buildings by taking into considerations the factors identified and also this board should behavior have rights to demolish buildings that are not up to standard.